2022
DOI: 10.1038/s41598-022-08273-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children with neurodevelopmental disorders and their parents during the COVID-19 pandemic: a 1-year follow-up study

Abstract: This study aimed to reveal changes in the quality of life (QOL) of children with neurodevelopmental disorders and their parents, and the interaction between their QOL and parental mental state during the coronavirus 2019 (COVID-19) pandemic. Eighty-nine school-aged children and parents participated in surveys in May 2020 (T1) and May 2021 (T2). The parents completed questionnaires that assessed their QOL, depression, parenting stress, and living conditions. Children’s temporary mood status was evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…The more social support mothers receive in relation to care of their children, the higher their family quality of life is (Kasser and Zia, 2020). Findings of the current study support the notion that the effect of having a child with disability on family quality of life is mediated by the resilience of the parents and the social support they receive (Ueda et al, 2022) and that social support is an important mediating variable in the relationship between resilience and quality of life (Mathew and Nair, 2017). This finding warrants the need for providing social services and psychological supports to children with disabilities and their families during the pandemic (Amor et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The more social support mothers receive in relation to care of their children, the higher their family quality of life is (Kasser and Zia, 2020). Findings of the current study support the notion that the effect of having a child with disability on family quality of life is mediated by the resilience of the parents and the social support they receive (Ueda et al, 2022) and that social support is an important mediating variable in the relationship between resilience and quality of life (Mathew and Nair, 2017). This finding warrants the need for providing social services and psychological supports to children with disabilities and their families during the pandemic (Amor et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…A main finding of the current study is that the quality of life of families who have children with disabilities decreased as the impact of the traumatic event (COVID-19 pandemic) increased. Studies conducted with families of children with different disabilities prior to or during the COVID-19 pandemic showed that families usually have lower levels of quality of life in comparison to families of children with typical development (Al Awaji et al, 2021;Ueda et al, 2022). For example, research has shown that families of children with intellectual disability (Bertelli et al, 2011), autism spectrum disorder (Cohen et al, 2014), cerebral palsy (Barros et al, 2019), and multiple disabilities (Chou et al, 2011) have relatively lower levels of quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, although family demographics, parent education, and parent being an essential worker were included in our predictive model, parent's mental health, recently reported to relate to children's outcome during the pandemic, [55][56][57][58] was not assessed. Second, although the aggregate sample includes youths with clinician-based diagnoses, previously collected measures of severity varied by contributing sample, and assessments of prior severity were based on parent responses in the AFAR survey.…”
Section: Discussionmentioning
confidence: 99%